The application of legislative frameworks for the management of medical records in Limpopo Province, South Africa. (September 2019) - Marutha, Ngoako
Medical records management needs to be governed using a legal framework to avoid records being lost, modified, altered, misfiled and/or damaged, since that may result in a struggle to locate them and wasting time. Medical records management, like any other field, has to be guided by a sound legislative framework. The application of legislation in the management of medical records can help safeguard privacy and confidentiality and curb the loss, modification, alteration, damage and misfiling of records. The study sought to assess the extent to which public hospitals in the Limpopo Province, South Africa apply legislation in the management of medical records. Quantitative data were collected using questionnaires completed by records management staff members in the hospitals of Limpopo. This study applied a quantitative research methodology and a survey research design. The study revealed that legal prescripts were not appropriately followed in the healthcare institutions due to a lack of fundamental resources. The study recommended, among other things, the provision of adequate resources and the appointment of suitably qualified records managers and staff or the development of staff capacity to ensure that appropriate legal frameworks are implemented adequately.